Shimalactone Biosynthesis Involves Spontaneous Double Bicyclo‐Ring Formation with 8π‐6π Electrocyclization. Issue 22 (20th March 2020) - Fujii, Isao; Hashimoto, Makoto; Konishi, Kaori; Unezawa, Akiko; Sakuraba, Haruka; Suzuki, Kenta; Tsushima, Harue; Iwasaki, Miho; Yoshida, Satsuki; Kudo, Akane; Fujita, Rina; Hichiwa, Aika; et al.
Abstract: Shimalactones A and B are neuritogenic polyketides possessing characteristic oxabicyclo[2.2.1]heptane and bicyclo[4.2.0]octadiene ring systems that are produced by the marine fungus Emericella variecolor GF10. We identified a candidate biosynthetic gene cluster and conducted heterologous expression analysis. Expression of ShmA polyketide synthase in Aspergillus oryzae resulted in the production of preshimalactone. Aspergillus oryzae and Saccharomyces cerevisiae transformants expressing ShmA and ShmB produced shimalactones A and B, thus suggesting that the double bicyclo‐ring formation reactions proceed non‐enzymatically from preshimalactone epoxide. DFT calculations strongly support the idea that oxabicyclo‐ring formation and 8π‐6π electrocyclization proceed spontaneously after opening of the preshimalactone epoxide ring through protonation. We confirmed the formation of preshimalactone epoxide in vitro, followed by its non‐enzymatic conversion to shimalactones in the dark. Abstract : Ringing off the hook : The shimalactone biosynthetic gene cluster was cloned and investigated. Expression of the ShmA polyketide synthase in A. oryza e resulted in production of preshimalactone. A. oryzae and S. cerevisiae transformants expressing ShmA and ShmB produced shimalactones A and B, thus suggesting that the double bicyclo‐ring formation reactions proceed non‐enzymatically from the preshimalactone epoxide, and this was supported by DFT calculations.